Spanish education system 2009 - Parras Laguna, Antonia (Ministerio de Educación, Cultura y Deporte. Área de Educación, 2012)
One of the main tasks of the Institute for Teacher Training and Educational Research and Innovation (IFIIE), is, since decades, the periodic preparation of reports describing the Spanish education system in a detailed and up-to-date way. This report constitutes a brief version of the one recently carried out by the IFIIE: The Spanish Education System 2009. Its methodology of work has been structured into three stages: 1) search, analysis, choice and classification of both state and regional regulations as well as official statistics, 2) juxtaposition of the information obtained, presented in tables and figures, and 3) comparison in order to understand and identify trends and convergences and divergences in state and regional education. As a result, two volumes with complex, thorough and detailed information on the education system and its different aspects are provided. This brief version consists of 14.